Animal-assisted therapy in a Canadian psychiatric prison. Issue 3 (29th August 2019) - Dell, Colleen; Chalmers, Darlene; Stobbe, Mark; Rohr, Betty; Husband, Alicia
Abstract : Purpose: Prison-based animal programs are becoming increasingly common in North America. The majority focus on community and animal well-being, with less explicit therapeutic goals for human participants. The purpose of this paper is to measure the objectives of a canine animal-assisted therapy (AAT) program in a Canadian psychiatric prison and examine whether the program supports inmates' correctional plans. Design/methodology/approach: A modified instrumental case study design was applied with three inmates over a 24-AAT-session program. Quantitative and qualitative AAT session data were collected and mid- and end-of-program interviews were held with the inmates, their mental health clinicians and the therapy dog handlers. Findings: Inmates connected with the therapy dogs through the animals' perceived offering of love and support. This development of a human–animal bond supported inmates' correctional plans, which are largely situated within a cognitive-behavioral skill development framework. Specifically, inmates' connections with the therapy dogs increased recognition of their personal feelings and emotions and positively impacted their conduct. Research limitations/implications: The findings suggest that prison-based AAT programs emphasizing inmate mental well-being, alongside that of animal and community well-being generally, merit further exploration. It would be worthwhile to assess this AAT program with a larger and more diverse sample of inmates and in a different institutional context and also to conduct a post-intervention follow-up. Originality/value: This is the first study of a prison-based AAT program in a Canadian psychiatric correctional facility.